Endorsement of Sharī'ah Label Product Influencers Through Social Media Efforts to Increase Interest in the Number of Muslim Consumers - Achmad Budi Susetyo; Md. Meraj Hasan (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2025)
The ease of people accessing information about a product has given rise to a new shopping system that can be done online. One of the social media applications that is currently often used is the TikTok application. It can be proven that Tiktok is the No. 1 application that is often downloaded in Indonesia according to Data Reports. The TikTok application algorithm is different from other applications, making it easier for people to go viral and be recognized by many people. Thus, the term influencer emerged as someone who can influence others. This study aims to examine and analyze the endorsement of Muslim influencers of fashion products through TikTok Shop social media to increase consumer interest. This study also explored how support affects economic outcomes for supporters and evaluates the impact of influencer marketing and content creators. This study used a library research method coupled with a data analysis framework rooted in Islamic economics and supported by inductive reasoning and qualitative data. The research findings revealed that influencers and content creators with significant followers have been shown to increase product sales significantly. The key factor for the success of social media promotion lies in implementing effective advertising strategies and collaborating with influential figures or media that resonate with target consumers. The existence of influencer support for a product significantly affects the number and interest of consumers so that it can improve the quality of marketing and increase the reach of a wide market.